2020
DOI: 10.1148/rg.2020190099
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative CT Analysis of Diffuse Lung Disease

Abstract: Quantitative analysis of thin-section CT of the chest has a growing role in the clinical evaluation and management of diffuse lung diseases. This heterogeneous group includes diseases with markedly different prognoses and treatment options. Quantitative tools can assist in both accurate diagnosis and longitudinal management by improving characterization and quantification of disease and increasing the reproducibility of disease severity assessment. Furthermore, a quantitative index of disease severity may serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 64 publications
0
73
0
1
Order By: Relevance
“…In addition, the authors thought a relatively large number of mild pneumonia could affect the results; hence, we compared the mild and severe pneumonia groups. Again, our NALP (−950 to −701 HU) reflects that the lungs are almost completely ventilated as compared to severely COVID-affected lung regions, and it suggests how well respiratory functions could be maintained in advanced pneumonia, especially in ARDS ( 9 ). The well-aerated lung region in severe COVID-19 pneumonia is substantially reduced in volume and might represent an important parameter for patients treated with a mechanical ventilator in ICU or those expired.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, the authors thought a relatively large number of mild pneumonia could affect the results; hence, we compared the mild and severe pneumonia groups. Again, our NALP (−950 to −701 HU) reflects that the lungs are almost completely ventilated as compared to severely COVID-affected lung regions, and it suggests how well respiratory functions could be maintained in advanced pneumonia, especially in ARDS ( 9 ). The well-aerated lung region in severe COVID-19 pneumonia is substantially reduced in volume and might represent an important parameter for patients treated with a mechanical ventilator in ICU or those expired.…”
Section: Discussionmentioning
confidence: 79%
“…Since the pathologic evaluation during the disease course of COVID-19 has not been established, computed tomography (CT) can reveal ground glass opacity and consolidation, which may reflect pathologic changes in these patients. Estimation of the volumetric quantification of chest CT images has been used in patients with various lung diseases including asthma, chronic obstructive pulmonary disease, interstitial lung disease, and oncological disease ( 9 10 11 ). Several studies have shown a potential role of chest CT volumetric quantification in predicting the mortality of ARDS ( 12 13 14 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…We used density threshold different than what suggested previously for ARDS, namely range form -900HU indicating nearly 90% gas and 10% tissue to -500HU indicating 50% gas and 50% tissue [28]. Again, our -950 to -700 HU range is intended for patients with respiratory I n P r e s s function at self-referral and indeed our definition reflects lung approximately completely ventilated as compared to severely compromised aerated lung in ARDS [14].…”
Section: Discussionmentioning
confidence: 99%
“…https://www.slicer.org) [13]. A fully automatic lung segmentation and analysis of lung parenchyma I n P r e s s segmentation (%S-WAL) was determined by density references from the literature, namely in the interval between -950 HU and -700 HU [14,15]. Furthermore, using the overall lung volume provided by software, the absolute volume of the well aerated lung (VOL-WAL) was calculated.…”
Section: Ct Images Analysismentioning
confidence: 99%
“…Among quantitative CT methods, those related to thoracic imaging are the most studied [20,22,23,[31][32][33][34][35][36][37][38][39][40][41][42][43]. In particular, the applications related to the classification and management of lung nodules are the most well-known and are used in both clinical practice and lung cancer screening programs [20,22,23,[31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%